Ecohydrological features and biodiversity status of estuaries in Bengal delta, Bangladesh: A comprehensive review - Rakib, Md. Refat Jahan; Hossain, Mohammad Belal; Islam, Mohammad Shahanul; Hossain, Iqbal; Rahman, Md. Mostafizur; Kumar, Rakesh; Sharma, Prabhakar (Frontiers in Environmental Science, 2022)
An estuary represents a transition point between freshwater and saltwater and has a complex but productive environment due to a strong interplay between geological, physical, chemical, and biological processes. In Bangladesh, the ecological factors and biodiversity of different estuaries have been investigated for the last 35 years. However, the data is widely scattered, not easily accessible, unpublished, and/or in the form of grey literature. In this study, an attempt has been made to aggregate information available on the geo-environmental and biodiversity status of estuaries for their sustainable management. The biological and environmental data of 21 estuaries along the Bangladesh coast were collected from previously published literature and analyzed. The analyses revealed that the estuarine environment of Bangladesh is very dynamic and diverse like other tropical estuaries. The physico-chemical and geological parameters in estuaries significantly varied due to monsoon patterns, nutrient influx, salinity intrusion, riverine discharge, siltation, and human interventions in estuaries. Among the key environmental variables, such as salinity (3.7-30 ppt), pH (7.04-8), DO (3.30-13.63 mg/L), and water temperature (21-30oC) varied. Over 830 faunal and floral species of 273 genera were recorded from the estuarine environment, including 208 fishes, 87 species of phytoplankton, and 67 species of zooplankton in this region. This study suggests the development of an appropriate policy to protect valuable, productive, and diverse ecosystems, especially for erosion control, pollution abatement, and habitat destruction, particularly in the mangrove forests and their associated habitats of Bangladesh.